2013
DOI: 10.1117/1.jbo.18.9.097009
|View full text |Cite
|
Sign up to set email alerts
|

Biospeckle in the human sclera and impact on laser speckle correlation measurement of eye tremor

Abstract: Ocular microtremor (OMT) is an involuntary fixational eye movement. We identify the implications of biospeckle for a noninvasive, laser speckle correlation technique to measure OMT. Biospeckle from the in-vivo eye is characterized and, using the resulting characteristics, a mathematical model to describe the biospeckle from the eye is designed and tested. Through in-vivo measurements, biospeckle is shown to disrupt the temporal stability of the speckle images over time. However, provided each speckle image is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Furthermore, when recording speckle from a living object, a form of time-varying speckle referred to as 'biospeckle' is expected. However, it has been shown that when recorded at a frame rate of 500 Hz, despite of the presence of biospeckle, the speckle captured from the eye sclera is reasonably stable between successive image frames and biospeckle alone has no systematic influence on the angular displacement measurement from the sclera (Kenny et al 2013a).…”
Section: Laser Speckle Correlation Metrologymentioning
confidence: 99%
“…Furthermore, when recording speckle from a living object, a form of time-varying speckle referred to as 'biospeckle' is expected. However, it has been shown that when recorded at a frame rate of 500 Hz, despite of the presence of biospeckle, the speckle captured from the eye sclera is reasonably stable between successive image frames and biospeckle alone has no systematic influence on the angular displacement measurement from the sclera (Kenny et al 2013a).…”
Section: Laser Speckle Correlation Metrologymentioning
confidence: 99%
“…Speculativeness notwithstanding, we believe that the proposal of testable hypotheses is a positive way to motivate the publicization of data and structure further empirical investigations in this area. Another high resolution non-contact FEM measurement method which can resolve tremor has recently been reported by Kenny et al ( 2013a , b ), so data of sufficient resolution may soon become available from this group.…”
Section: Fixational Eye Movementsmentioning
confidence: 99%